In-hospital mortality in SARS-CoV-2 stratified by the use of corticosteroid. (August 2022) - Alotaibi, Naser; Alroomi, Moudhi; Aboelhassan, Wael; Hussein, Soumoud; Rajan, Rajesh; AlNasrallah, Noor; Al Saleh, Mohammad; Ramadhan, Maryam; Zhanna, Kobalava D.; Pan, Jiazhu; Malhas, Haya; Abdelnaby, Hassan; et al.
Аbstrасt: Objective: To investigate COVID-19 related mоrtаlity according to the use of corticosteroid therapy. Design: Retrospective cohort study. Setting: Two tertiary hospitals in Kuwait. Participants: Overall, 962 patients with confirmed SARS-CoV-2 infection, were stratified according to whether they were treated with corticosteroids (dexamethasone or methylprednisolone). The mean age of the patients was 50.2 ± 15.9 years and 344/962 (35.9%) were female. Main outcome measures: In-hospital mortality and cumulative all-cause mortality. Results: Compared to non-corticosteroid therapy patients, corticosteroid therapy patients had a higher prevalence of hypertension, diabetes mellitus, cardiovascular disease, chronic lung disease, and chronic kidney disease; a longer hospital stay (median [IQR]: 17.0 [5.0–57.3] days vs 14.0 [2.0–50.2] days); and a higher in-hospital mortality (51/199 [25.6%] vs 36/763 [4.7%]). Logistic regression analysis showed a higher in-hospital mortality in the corticosteroid group (adjusted odds ratio [aOR]: 4.57, 95% confidence interval [CI]: 2.64–8.02, p < 0.001). Cox proportional hazards regression showed that corticosteroid use was a significant predictor of mortality (hazard ratio [HR]: 3.96, p < 0.001). Conclusions: In-hospital mortality in patients with SARS-CoV-2 on corticosteroid therapy was 4.6 times higher than in those without corticosteroid therapy. Highlights: In-hospital mortality in patients with SARS-CoV-2 on corticosteroid was evaluated. Risk of mortality was 4.6 times higher in those with corticosteroid therapy. Corticosteroid therapy patients had a longer hospital stay.